História da educação indígena na província de Mato Grosso - Pesovento, Adriane (2014)
Studies the history of the indigenous education in province Mato Grosso between 1834 and 1889, focusing the mechanisms of imposition of the westcentric and eurocentered paradigm on indigenous people, at the same time seeks to show the practices of resistance embraced by different ethnic groups in position to established. The aim of research also is to present the characteristics of the indigenous education understood as pedagogical practices overlapped and constructed from diverse doing-livings own these cultures and that may be noticed from cosmology, religiousness, non-material and material culture, system of kinship among other specific aspects of indigenous ethnic groups studied and that also pose as educational factors. To find and discuss educational practices in a more remote time, i. e, between mid-eighteenth century and eight years, was necessary to study the speeches of memoirs, observing the proper and necessary caveats to their interpretation, given the time of its production. Have other sources such as the reports of travelers, Reports of General Officers of the Indians and Officials Speeches (Reports of the Presidents of the Province), also sought to capture from sparks, the evidence would realize that fragments of this educational universe is somewhat muted in the records. Furthermore, there is concern in historicizing what was understood as indigenous education, supported politically by the indigenous law of Brazil Empire, namely, Regulations, Decrees, among others.The central hypothesis stands out for the perception of education at various times confused with the civilizational discourse and its close relations with the use of native labor for the benefit of local society. The research demonstrated the realization that there was a whole effort to exert control over the various ethnic groups seeking to colonize this knowledge, despite the rudimentary school experience that drew the period. The purpose of submitting is perceived both in speeches by authorities as the actions of religious or even, in the appropriation of indigenous labor by the surrounding society that assumed the role of "civilizing" the natives while trying to promote chimera then called: modernity in the Province. To understand the research object, is adopted as the theoretical foundation the perspective of the coloniality of knowledge in the studies Edgardo Lander, Aníbal Quijano and Walter Mignolo, as well as discussions of Immanuel Wallerstein and authors that are borrowed from anthropology to the understanding of subject of a thesis and without whom the study would not be possible. The documentary sources used were raised and organized from the Public Archives of Mato Grosso (APMT), the Indian Museum - National Fudação of Indio - (FUNAI-RJ), the National Archives of Rio de Janeiro (ANRJ), the Center for Regional documentation and Historical Information (NDHIR-UFMT), Records 12 of the Journal of the Brazilian Historical and Geographical Institute - RHGB and works as Couto de Magalhães titled "the Wild" written in the late nineteenth century and still reports of travelers passed by the Province in the period leaving their impressions. The discussions also expressed in the work represent a split in the line of coloniality of knowledge, which is also a bias studies conducted by the Research Group Education History and Memory - GEM / PPGE/UFMT.